Reflections on the role of nudges in human-computer interaction for behavior change - da Cunha, José Adson Oliveira Guedes; Aguiar, Yuska Paola Costa (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
Considering the increase in the use of digital technologies, there is also an increase in the number of decisions made through these ways. In this context, designers must understand the effects of their interfaces on users' decisions, thus acting as choice architects. Digital nudges are presented as tools to enable people to change their behavior in a predictable way without prohibiting options. Although they have similarities with persuasive technologies, such aspects of the choice architecture have new characteristics. This work intends to generate reflections on the adoption of digital nudges in the different aspects of Human- Computer Interaction.